The Religious Approach Prevents Threat of Environmental Damage - Kusuma Kusuma; Syamsul Maarif; Pujo Widodo; Wilopo Wilopo (CV. AFDIFAL MAJU BERKAH, 2023)
Protection against the threat of damage to the natural environment, is more often faced with the creation of laws and regulations to prevent it. However, the rules made are more defeated by economic factors, domestic and world market needs. Likewise, the protection and management of the environment and natural resources relies heavily on economic factors as the main motive which subordinates norms and ethical factors. Many environmental experts are of the opinion that practical and technical measures to protect and manage the environment and natural resources that only rely on scientific and technological assistance are not the right solution. Then various solutions are offered to prevent environmental damage, including through the theory of adaptation. Another offer is through a religious teaching approach because the assumption is that through the argument of the holy book, excessive exploitation of nature and damage to the environment due to human actions can be prevented and is an important alternative. This research will discuss whether a religious approach can be effective in avoiding damage to the surrounding natural environment or not using a literature review technique. The results show that the verses and hadiths of the Prophet Muhammad actually invite mankind to listen, think, and be grateful for God's creation by utilizing nature, the environment and protecting the environment. Hence, the conclusion is religious approach can contribute to regional development in the era of regional autonomy freedom in facing environmental preservation in the midst of a very sharp and ruthless global capitalism. Even though the dominant form of this knowledge in modern society is not religious, but religion legitimizes social institutions and orders by giving them ontological status. Thus, the Ulama Fatwa in dealing with environmental damage is an important step to maintain a better life.